Evaluasi Volume Pasangan Dinding Menggunakan Clash Detection Pada Proyek Hotel Marriot Gelora - Era Agita Kabdiyono; Rosario Olsen (Jurnal Teknik dan Science, 2025)
The development of digital technology has a positive impact on the construction world, which plays an important role in economic growth and employment. The complexity of construction work requires good project management and coordination to simplify and minimize errors in the construction and supervision process. One technology that can be implemented in construction work is Building Information Modeling (BIM). This study uses a quantitative method using BIM software, namely Autodesk Revit for 3D modeling and Autodesk Navisworks for analyzing collisions (clash detection). Data collection techniques are carried out by receiving detailed engineering drawing (DED) data from consultants, 3D model structures, architecture and a recapitulation of project cost estimates. The use of BIM in the Marriot Gelora Jakarta hotel project specifically to emit basement wall volumes uses the clash detection method found in Autodesk Navisworks software. Clash detection analysis is only carried out on the basement floor (B4 - B1M). A clash case is created related to the volume of the basement architectural wall. Based on the results of the calculation of the budget plan for the basement floor architectural wall work before and after clash detection, it can be concluded that the use of BIM clash detection technology can save budget costs of Rp. 82,191,346.13.